2018
DOI: 10.1016/j.ymthe.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Advanced siRNA Designs Further Improve In Vivo Performance of GalNAc-siRNA Conjugates

Abstract: Significant progress has been made in the advancement of RNAi therapeutics by combining a synthetic triantennary N-acetylgalactosamine ligand targeting the asialoglycoprotein receptor with chemically modified small interfering RNA (siRNA) designs, including the recently described Enhanced Stabilization Chemistry. This strategy has demonstrated robust RNAi-mediated gene silencing in liver after subcutaneous administration across species, including human. Here we demonstrate that substantial efficacy improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
234
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(241 citation statements)
references
References 31 publications
6
234
0
1
Order By: Relevance
“…Accordingly, another GalNAc-siRNA conjugate targeting TTR, vutrisiran (ALN-TTRsc02), will be used to further explore the benefit-risk profile of RNAi therapeutics across the full spectrum of ATTR amyloidosis, including patients with hereditary and wt cardiomyopathy. Compared with revusiran, which is a first-generation (standard template chemistry) GalNAc-siRNA conjugate, and thus prone to rapid in vivo nuclease-mediated degradation, vutrisiran is a secondgeneration compound (enhanced stabilization chemistry [ESC]), with far greater metabolic stability leading to significantly augmented potency and durability [27]. As such, the exposure to revusiran, given at 500-mg weekly doses in the ENDEAVOUR study, was 28 g of siRNA in the first year, whereas vutrisiran achieves the same degree of TTR reduction at 25 mg every 3 months (100 mg annually), equating to a 280-fold lowered drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, another GalNAc-siRNA conjugate targeting TTR, vutrisiran (ALN-TTRsc02), will be used to further explore the benefit-risk profile of RNAi therapeutics across the full spectrum of ATTR amyloidosis, including patients with hereditary and wt cardiomyopathy. Compared with revusiran, which is a first-generation (standard template chemistry) GalNAc-siRNA conjugate, and thus prone to rapid in vivo nuclease-mediated degradation, vutrisiran is a secondgeneration compound (enhanced stabilization chemistry [ESC]), with far greater metabolic stability leading to significantly augmented potency and durability [27]. As such, the exposure to revusiran, given at 500-mg weekly doses in the ENDEAVOUR study, was 28 g of siRNA in the first year, whereas vutrisiran achieves the same degree of TTR reduction at 25 mg every 3 months (100 mg annually), equating to a 280-fold lowered drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNAs used in these studies were fully chemically modified for maximal stability and minimal innate immune activation as described (see Figure 1a and Methods). We and others have recently shown that full chemical stabilization is essential for conjugated-mediated delivery [19][20][21] . The chemical compositions of lipids had a profound effect on the hydrophobicity of lipid-siRNA, based on retention time in reversed-phase HPLC 36 , which ranged from 1 to 12.2 minutes (Figure 1b).…”
Section: Synthesis Of Conjugated Sirnas Librarymentioning
confidence: 99%
“…Thus, full chemical stabilization of siRNAs is essential for conjugate-mediated delivery 19 . The clinical success of GalNAc conjugated siRNAs was only achieved when the siRNAs are extensively modified 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions, primarily limited to antisense nucleotides (which are distinct from siRNA) [10], siRNA therapies have been well tolerated and efficacious. Advances in siRNA biochemistry [11] and improved delivery vehicles [12] raise the exciting prospect that once yearly injections to treat genetic disease are within reach.…”
Section: Rna Therapies Are Limited By Inefficient Delivery To Target mentioning
confidence: 99%